Programa Paulista de Análise Fiscal de Alimentos - César Latorre, Willian; Venturi, Denise; Azucena Castro Blanco Pytel, Delfina; Pinati Marsiglia, Deise Aparecida; Marques Santos, Cecília Cristina (BEPA. Boletim Epidemiológico Paulista, 2004)